2021
DOI: 10.2196/26235
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Experiences of Behavior Change Support in a Digital Fall Prevention Exercise Program: Qualitative Study Framed by the Self-determination Theory

Abstract: Background Exercise is an effective intervention to prevent falls in older adults; however, long-term adherence is often poor. To increase adherence, additional support for behavior change has been advocated. However, consistency in the reporting of interventions using behavior change techniques is lacking. Recently, a classification system has been developed to increase consistency in studies using behavior change techniques within the self-determination theory. O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 43 publications
(67 reference statements)
0
47
0
Order By: Relevance
“…Therefore, the virtual coach was also created as an attempt to increase relatedness with the system. This expectation was confirmed in a qualitative evaluation of the behavior change support in the Safe step application (49). Experiences from a telecare intervention for older adults support the concept of relatedness with digital systems and suggest the utility of a broadened concept of relatedness beyond humanhuman interaction (50).…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, the virtual coach was also created as an attempt to increase relatedness with the system. This expectation was confirmed in a qualitative evaluation of the behavior change support in the Safe step application (49). Experiences from a telecare intervention for older adults support the concept of relatedness with digital systems and suggest the utility of a broadened concept of relatedness beyond humanhuman interaction (50).…”
Section: Discussionmentioning
confidence: 85%
“…Instructions for this were given in the videos and to be based on their own evaluations. The application includes “tools” to support behavior change in the form of an integrated calendar for planning and monitoring exercise activity ( 24 ). An integrated virtual physiotherapist provides reminders and feedback after each exercise session.…”
Section: Methodsmentioning
confidence: 99%
“…Safe Step is a fully self-managed digital exercise programme developed in co-creation with older people who were 70 years of age or older ( 23 ). A four-month feasibility study showed that participants who exercised with the Safe Step were more satisfied with the support than participants exercising with a self-managed booklet format ( 24 ). One year after the start of the intervention, participants who exercised with the digital programme were more likely to continue to exercise regularly (67%) than participants in the booklet group (35%) ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, what is known from past research is that basic psychological needs satisfaction may moderate the relationship between ICT use and emotion ( Allen and Anderson 2018 ; Przybylski et al 2009 ; Fang et al 2019 ; James et al 2022 ; Partala and Kallinen 2012 ; Pettersson et al 2021 ). For example, Przybylski et al ( 2009 ) found that when people’s basic psychological needs are satisfied, they will have a better experience when playing games on ICT; however, when their satisfaction with basic psychological needs is low, they will experience negative emotions such as stress when playing games with ICT.…”
Section: Introductionmentioning
confidence: 99%
“…Current research states that autonomy needs satisfaction may moderate the association between ICT use and emotional experience for older adults. Pettersson et al ’s ( 2021 ) study using an exercise app as a research tool found that when older adults’ autonomy needs were satisfied, they felt that it was very meaningful to use the app. Conversely, when older adults’ autonomy needs were not met, they experienced negative emotions such as anxiety when using ICT ( Di Giacomo et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%